Beginning C# Object-Oriented Programming - Clark, Dan (The Expert's Voice IN .NET, 2013)
Learn C# with Beginning C# Object-Oriented Programming and you'll be thinking about program design in the right way from day one. Whether you want to work with .NET for the web or desktop, or for Windows 8 on any device, Dan Clark's accessible, quick-paced guide will give you the foundation you need for a successful future in C# programming. In this book you will: Master the fundamentals of object-oriented programming Work through a case study to see how C# and OOP work in a real-world application Develop techniques and best practices that lead to efficient, reusable, elegant code Discover how to transform a simple model of an application into a fully-functional C# project. With more than 30 fully hands-on activities, Beginning C# Object-Oriented Programming teaches you how to design a user interface, implement your business logic, and integrate your application with a relational database for data storage. Along the way, you will explore the .NET Framework, ASP.NET and WinRT. In addition, you will develop desktop, mobile and web-based user interfaces, and service-oriented programming skills, all using Microsoft's industry-leading Visual Studio 2012, C#, the Entity Framework, and more. Read this book and let Dan Clark guide you in your journey to becoming a confident C# programmer.